Intonational Variation in the North-West of England: The Origins of a Rising Contour in Liverpool. (December 2022) - Nance, Claire; Kirkham, Sam; Lightfoot, Kate; Carroll, Luke
This paper investigates intonation in the urban dialect of Liverpool, Scouse. Scouse is reported to be part of a group of dialects in the north of the UK where rising contours in declaratives are a traditional aspect of the dialect. This intonation is typologically unusual and has not been the subject of detailed previous research. Here, we present such an analysis in comparison with Manchester, a city less than 40 miles from Liverpool but with a noticeably different prosody. Our analysis confirms reports that rising contours are the most common realization for declaratives in Liverpool, specifically a low rise where final high pitch is not reached until the end of the phrase. Secondly, we consider the origin of declarative rises in Scouse with reference to the literature on new dialect formation. Our demographic analysis and review of previous work on relevant dialects suggests that declarative rises were not the majority variant when Scouse was formed but may have been adopted for facilitating communication in a diverse new community. We highlight this contribution of intonational data to research on phonological aspects of new dialect formation, which have largely considered segmental phonology or timing previously.